ARMENIAN GRAVESTONES. SÁNDOR KÁNYÁDI’S POETRY TOWARDS THE TRANSFORMATION - Piotrowiak-Junkiert, Kinga (Porównania, 2014)
The article concerns poetry of Sándor Kányádi, one of the most famous and influential Hungarian writers from Transylvania. The main purpose of the article is to analyse the political persecution of the communist dictatorship in Romania against Hungarian writers and to estimate the meaning of the period of political changes 1989/90. The author interprets the poem Armenian gravestones from the collection Mane and skull, in which Kányádi gave up his earlier idyllic poetics and chose a poetry of bitter consciousness of the world’s constant change. In the interpretation of the poems, the author focuses on explaning a few crucial terms as for example: „Transylvanian landscape”, decline of memory about national minorities and homeland in the poetry of Kányádi.